Strengthening the Profile of Pancasila Students Based on Local Wisdom - Karim, Herlis Setiawan; Mas, Sitti Roskina; Zulystiawati, Zulystiawati (Faculty of Education Universitas Negeri Malang, 2023)
This study aims to describe (1) the form of local wisdom for strengthening the values of the Pancasila Student Profile for students in Driving School, (2) the implementation of the Project to students, and (3) the implications of the Project on students’ characters. This study used a qualitative approach with a case study design. The research informants were school principals, homeroom teachers, project administrators, and students of Class I and Class IV. The determination of data sources was carried out by purposive sampling. Data collection obtained from interviews, observation, and document study. Data analysis used reduction, display, and data verification. The validation of data was conducted through data credibility by extending the observation period, and triangulation (sources, techniques, and experts). The results of the study showed that: (1) the form of local wisdom were (a) traditional games, folklore, and embroidery crafts; (2) the implementation of the Project for students began with activities of meeting with the project facilitation team and parental socialization, reference studies, module development, implementation in teaching and learning, showcasing/presentation of work, and evaluation and reflection; (3) the implications of the Project for students’ characters was the formation of pancasila student profile with the dimensions of global diversity, critical thinking, independence, and mutual cooperation